The Dutch East India Company and the economy of Bengal, 1630-1720 - Prakash, Om, 1940- (Princeton legacy library., 1985)
Om Prakash reveals the central role played by Bengal in the Dutch East India Company's activities in India in the seventeenth and the early eighteenth century and the resulting integration of India into the world economy. Originally published in 1985. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.